Open urethroplasty versus endoscopic urethrotomy - clarifying the management of men with recurrent urethral stricture (the OPEN trial): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Stephenson, Rachel; Carnell, Sonya; Johnson, Nicola; Brown, Robbie; Wilkinson, Jennifer; Mundy, Anthony; Payne, Steven; Watkin, Nick; N'Dow, James; Sinclair, Andrew; Rees, Rowland; Barclay, Stewart; et al.
Abstract Background Urethral stricture is a common cause of difficulty passing urine in men with prevalence of 0.5 %; about 62, 000 men in the UK. The stricture is usually sited in the bulbar part of the urethra causing symptoms such as reduced urine flow. Initial treatment is typically by endoscopic urethrotomy but recurrence occurs in about 60 % of men within 2 years. The best treatment for men with recurrent bulbar stricture is uncertain. Repeat endoscopic urethrotomy opens the narrowing but it usually scars up again within 2 years requiring repeated procedures. The alternative of open urethroplasty involves surgically reconstructing the urethra, which may need an oral mucosal graft. It is a specialist procedure with a longer recovery period but may give lower risk of recurrence. In the absence of firm evidence as to which is best, individual men have to trade off the invasiveness and possible benefit of each option. Their preference will be influenced by individual social circumstances, availability of local expertise and clinician guidance. The open urethroplasty versus endoscopic urethrotomy (OPEN) trial aims to better guide the choice of treatment for men with recurrent urethral strictures by comparing benefit over 2 years in terms of symptom control and need for further treatment. Methods/Design OPEN is a pragmatic, UK multicentre, randomised trial. Men with recurrent bulbar urethral strictures (at least one previous treatment) will be randomised to undergo endoscopic urethrotomy or open urethroplasty. Participants will be followed for 24 months after randomisation, measuring symptoms, flow rate, the need for re-intervention, health-related quality of life, and costs. The primary clinical outcome is the difference in symptom control over 24 months measured by the area under the curve (AUC) of a validated score. The trial has been powered at 90 % with a type I error rate of 5 % to detect a 0.1 difference in AUC measured on a 0–1 scale. The analysis will be based on all participants as randomised (intention-to-treat). The primary economic outcome is the incremental cost per quality-adjusted life year. A qualitative study will assess willingness to be randomised and hence ability to recruit to the trial. Discussion The OPEN Trial seeks to clarify relative benefit of the current options for surgical treatment of recurrent bulbar urethral stricture which differ in their invasiveness and resources required. Our feasibility study identified that participation would be limited by patient preference and differing recruitment styles of general and specialist urologists. We formulated and implemented effective strategies to address these issues in particular by inviting participation as close as possible to diagnosis. In addition re-calculation of sample size as recruitment progressed allowed more efficient design given the limited target population and funding constraints. Recruitment is now to target. Trial registration ISRCTN98009168 Date of registration: 29 November 2012.